Day-time variation of serum periostin in asthmatic adults treated with ICS/LABA and adults without asthma. Issue 1 (December 2017) - Caswell-Smith, Rachel; Cripps, Terrianne; Charles, Thom; Hosking, Alexander; Handigol, Meghana; Holweg, Cecile; Matthews, John; Holliday, Mark; Maillot, Corentin; Fingleton, James; Weatherall, Mark; Beasley, Richard; et al.
Abstract Background We aimed to determine the effect of sampling time during the day on serum periostin levels in adult participants with and without asthma. Methods Serum periostin was measured at 2-h intervals from 0800 to 1800 h in 16 adult participants with stable asthma prescribed inhaled corticosteroid and long-acting beta-agonist therapy, and in 16 otherwise healthy participants without asthma. Mixed linear models were used to compare time zero (08:00 h) with subsequent measurement time for serum periostin for both groups. Results In both asthma and non-asthma, the mean (SD) serum periostin levels continuously reduced during the day from 53.5 (13.6) ng/mL at 0800 h to 50.9 (13.4) ng/mL at 1800 h (difference log periostin −0.05, P ≤ 0.001) and 50.5 (13.0) ng/mL at 0800 h to 46.2 (11.5) ng/mL at 1800 h (difference log periostin −0.08, P ≤ 0.001) respectively. Conclusions Periostin values are higher in the morning compared with the afternoon in asthmatic and non-asthmatic adults. The small magnitude of the variation in serum periostin levels suggests that the time of day in which the serum periostin measurements are made is unlikely to influence treatment decisions if a specific serum periostin level is used to predict treatment responsiveness. Trial registration Australia New Zealand Trials Registry (ACTRN12614000072617)